2020
DOI: 10.18203/2394-6040.ijcmph20200436
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination coverage of children in tribal Narmada district of Gujarat: a cross sectional study

Abstract: Background: Vaccination being one of the cheapest and safest methods of primary prevention, indicators of maternal and child healthcare are crucial. Multi-indicator cluster survey was planned to check these objectives as set up in reproductive child health (RCH)-II and National Rural Health Mission (NRHM) plan. This study was initiated to determine the vaccination coverage among the children in tribal district in Gujarat and to determine factors associated with partial immunization and non-immunization.Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 7 publications
1
5
0
Order By: Relevance
“…This study found that full immunization coverage among young children from the communities experiencing disadvantage in Vellore was 65% and 77% using information based on vaccination cards or parental recall and vaccination cards alone, respectively. These coverage estimates are similar to recent studies among migrant (67%), tribal (78%), and slum (72%) populations in other parts of India, but lower than the prescribed Mission Indradhanush target of 90% [9,[29][30][31]. Previous studies from India predominantly report coverage estimates combining vaccination cards and parental recall information [12,22,29,[32][33][34][35].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…This study found that full immunization coverage among young children from the communities experiencing disadvantage in Vellore was 65% and 77% using information based on vaccination cards or parental recall and vaccination cards alone, respectively. These coverage estimates are similar to recent studies among migrant (67%), tribal (78%), and slum (72%) populations in other parts of India, but lower than the prescribed Mission Indradhanush target of 90% [9,[29][30][31]. Previous studies from India predominantly report coverage estimates combining vaccination cards and parental recall information [12,22,29,[32][33][34][35].…”
Section: Discussionsupporting
confidence: 84%
“…We also found a positive but non-significant association between parental familiarity with the vaccination schedule and children's vaccination status in the multivariate analysis. Many previous studies among migrant, tribal, and slum-dwelling communities in India report a lack of parental awareness about the vaccination schedule, place of vaccination, and the need for vaccination frequently as reasons for children being partially vaccinated or unvaccinated [12,29,31,35,44]. Parents who participated in the FGDs in our study were generally aware of the benefits of vaccination and could list a few vaccines from the routine immunization schedule.…”
Section: Discussionmentioning
confidence: 73%
“…Some other studies also reported a lower proportion of tribal children being fully vaccinated. About 3% of children aged 12–23 months in tribal communities reported not being vaccinated in the Narmada districts of Gujarat [18]. NFHS‐5 reported that approximately 4% of children that belonged to tribes did not receive a single vaccine, and the national average of unvaccinated children was 3.6% [3].…”
Section: Discussionmentioning
confidence: 99%
“…Health service provision characteristics were significantly associated with a child being fully vaccinated. A child born in a health facility was six times more likely to be fully vaccinated than those born at home (AOR being vaccinated in the Narmada districts of Gujarat [18]. NFHS-5 reported that approximately 4% of children that belonged to tribes did not receive a single vaccine, and the national average of unvaccinated children was 3.6% [3].…”
Section: Vaccination Statusmentioning
confidence: 99%
See 1 more Smart Citation